Clinical analysis on the early complications after carotid endarterectomy - Mao-zhen BU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
Objective To analyze the influencing factors of early complications after carotid endarterectomy (CEA), in order to evaluate the early safety after CEA. Methods A total of 396 patients with carotid stenosis underwent 407 CEAs, and the complications within 30 d after CEA were analyzed. Univariate and backward multivariate Logistic regression analysis were used to evaluate the related risk factors for major adverse events within 30 d after CEA.  Results The success rate of 407 CEAs was 100%. Major complications within 30 d after CEA occurred in 18 cases (4.42%), including 5 cases (1.23%) of death, 8 cases (1.97% ) of ischemic stroke and 5 cases (1.23% ) of cerebral hemorrhage. Secondary complications occurred in 98 cases (24.08%). Logistic regression analysis revealed smoking (P = 0.039) and modified Rankin Scale (mRS) score on admission ≥ 3 (P = 0.001) were the independent risk factors for early adverse events (within 30 d) after CEA.  Conclusions CEA is a safe surgical method with a low incidence rate of postoperative complications, which could be decreased by improving surgical skills and gathering surgical experiences. Smoking and mRS score on admission ≥ 3 can increase the risk of CEA.   DOI: 10.3969/j.issn.1672-6731.2015.04.009